Pembangkitan Decoupled Residual untuk Isolasi Kesalahan Aktuator Pesawat Terbang Bergerak Lateral - Samiadji Herdjunanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Implementation of time scheduled maintenance is not suitable if it is applied for systems with many varieties of heavy workload and harsh environment, since on that condition components degrade earlier than those under normal condition. Therefore, it has been shifted to condition-based maintenance (CBM). One important aspect, among others, toward successfull implementation of CBM method is fault isolation. The problem to be investigated is related to generate decoupled residual for actuator fault isolation of an aircraft on lateral movement. The proposed solution for that problem is to implement combination of transformation matrix and special filter. Transformation matrix is used to convert feature locations of actuator faults to signature vectors. Moreover, the signature vectors will be processed further by the special filter to generate decoupled residuals. It is assumed that the actuator is the only fault when the aircraft is on lateral movement. The results show that special filter and transformation matrix can be designed so that the residual of aileron actuator fault is decoupled from the residual of rudder actuator fault.